Fighting global poverty. Issue 4 (3rd January 2018) - Pogge, Thomas
Abstract: Many different indicators are used to monitor poverty and poverty-related deprivations. Two kinds of legitimacy worries may arise about any such indicator: one regarding its reliability as a measure of progress and another regarding the uses to which it is being put. This essay will touch upon both worries, beginning with the latter.